ANALISIS DAN PERANCANGAN SISTEM LAYANAN DAN RESERVASI TIKET BUS ONLINE MELALUI PENDEKATAN BERBASIS WEBSITE - Palma Juanta; Windania Purba; Evta Indra; Mario Gota Manalu; Aguan Aritonang (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
In this day and age the bus is the most common means of transportation used by the community because of the low price and easy way of ordering simple and accurate and still affordable for the economic community middle down. Generaly bus ticket bookings are made with go directly to the point of sale of bus tickets or by calling to the counter office. This ordering process has a weakness, namely the clerk or managers have difficulty recording, and errors often occur when recording ticket reservations. Regarding the time of ordering, usually prospective travelers book tickets a day or two before departure, and some are don't book tickets a few days in advance and buy tickets on the day departures, which often results in them not getting tickets that are society wants. The aim of this work is to design the system online bus ticket reservation developed using an application. Program it is built using Python programming and machine learning to make it easier to generate data automatically and make predictions Accurate. The result of this research is a bus ticket reservation system which offers a new alternative to the bus ticket booking process without distance and time constraints. In addition, the public will also receive information regarding bus schedules, ticket prices, and possible changes to departures bus.